2021
DOI: 10.1108/jabs-06-2020-0237
|View full text |Cite
|
Sign up to set email alerts
|

HRD practices, employee competencies and organizational effectiveness: role of organizational learning culture

Abstract: Purpose This paper aims to examine the moderating role of organizational learning culture (OLC) on the relationship between human resource development (HRD) practices and employee competencies (EC) in enhancing organizational effectiveness (OE). Design/methodology/approach An integrated research model of HRD practices, EC, OE and OLC was developed. The validity of the model is tested by applying structural equation modelling (SEM) approach to data collected from 506 employees working in 4 medium-size cement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 95 publications
(66 reference statements)
0
27
0
1
Order By: Relevance
“…Woodard's (2007) research showed that employees who could self-direct their new hire training had nearly 20% higher engagement and satisfaction scores with training than those who could not. While self-determination theory (SDT) as proposed by Deci et al (2017) and experiential learning theory could explain how gamified learning could better appeal to employees, the role of an organization's learning climate (OLC) was also found to be crucial to whether people accept and transfer training to the workplace (Potnuru et al, 2021). Social cognitive theory (SCT) also plays a critical role, especially for older adults and using smart devices or gamification (Choudrie et al, 2021).…”
Section: Workplace Learningmentioning
confidence: 99%
“…Woodard's (2007) research showed that employees who could self-direct their new hire training had nearly 20% higher engagement and satisfaction scores with training than those who could not. While self-determination theory (SDT) as proposed by Deci et al (2017) and experiential learning theory could explain how gamified learning could better appeal to employees, the role of an organization's learning climate (OLC) was also found to be crucial to whether people accept and transfer training to the workplace (Potnuru et al, 2021). Social cognitive theory (SCT) also plays a critical role, especially for older adults and using smart devices or gamification (Choudrie et al, 2021).…”
Section: Workplace Learningmentioning
confidence: 99%
“…Out of all the resources, the HR is the active element that can accelerate the effective utilization of other resources too. Employee competencies play a critical role in human resource development (HRD), which can lead to increased organizational effectiveness (Potnuru and Sahoo, 2016; Shet et al , 2019; Potnuru et al , 2021). Organizational effectiveness talks about how well the organization is in for achieving what it desires for (Etzioni, 1959).…”
Section: Step 1: Identification Of Units (Work-life Integration Job C...mentioning
confidence: 99%
“…The first study was conducted by Potnuru et al (2020), the results show a significant and positive relationship between employee competencies and employee perceived organizational effectiveness. (The results showed a significant and positive relationship between employee competence and perceived organizational effectiveness of employees).…”
Section: Literature Reviewmentioning
confidence: 99%